2006
DOI: 10.1016/j.ejvs.2006.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Grafts and Graft Materials as Vascular Substitutes for Haemodialysis Access Construction

Abstract: Apart from long-term central venous catheterisation, the insertion of an arteriovenous graft (AVG) remains the only option to allow continued haemodialysis when the patient's superficial veins have been exhausted. Although, expanded PTFE has become the graft of choice for haemodialysis access throughout the world, many other organic or semi-organic materials are currently available for AVG construction. These are less prone to steal syndrome, easier to handle, more resistant to infection and may have similar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 59 publications
1
39
0
2
Order By: Relevance
“…4 However, xenografts (eg, bovine ureteric graft) used in complex hemodialysis access surgery are frequently complicated with true aneurysm formation and subsequent online thrombosis, leading to access failure. 34 Furthermore, the incidence of false aneurysms and puncture site complications is reportedly higher for nonreinforced PTFE grafts than for reinforced PTFE grafts. 26 It has been suggested that a careful needle puncture technique, frequent rotation of puncture sites, and the use of rigorous aseptic methods are fundamental to preserving the long-term structural integrity of an AVA and decreasing the incidence of false aneurysm formation.…”
Section: Resultsmentioning
confidence: 99%
“…4 However, xenografts (eg, bovine ureteric graft) used in complex hemodialysis access surgery are frequently complicated with true aneurysm formation and subsequent online thrombosis, leading to access failure. 34 Furthermore, the incidence of false aneurysms and puncture site complications is reportedly higher for nonreinforced PTFE grafts than for reinforced PTFE grafts. 26 It has been suggested that a careful needle puncture technique, frequent rotation of puncture sites, and the use of rigorous aseptic methods are fundamental to preserving the long-term structural integrity of an AVA and decreasing the incidence of false aneurysm formation.…”
Section: Resultsmentioning
confidence: 99%
“…Various materials -autologous, homologous and heterologous -are used as a graft. Various evaluations of these materials have been reported but the common view is that all are associated with a large number of complications [3][4][5] . Currently, the ePTFE conduit is preferred for its availability.…”
Section: Introductionmentioning
confidence: 99%
“…In 1973, Volder was the first to use the eP-TFE conduit as an arteriovenous graft for hemodialysis 8 . In the course of time ePTFE conduit has became the gold standard for arteriovenous graft 5,[9][10][11][12] . Currently, there are many ePTFE conduits producers and various product modifications are available.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the homologous saphenous vein, I tried every type of commercially organic, semi-organic or synthetic vascular prostheses for constructing HD accesses, such as bovine carotid artery, human umbilical vein, PTFE, polyurethane, and I abandoned some of them favoring new materials, such as ovine collagen with polyester mesh, mesenteric bovine vein and new bovine ureter. These biological materials demonstrate less anastomotic site compliance mismatch, a reduced tendency to thrombose, reduced intimal hyperplasia at the venous end of the AVG, a reduced risk of steal syndrome due to the ability to "pleat" the graft thereby reducing its diameter to match a smaller arteriotomy (78), a reduced risk of infection, a considerable reduction in re-operations to maintain the patency and better results than PTFE. Currently, in Italy we cannot use commercially homologous saphenous veins, successfully used by us in the past and which are commonly traded in France, because according to a controversial lawful statement, it is considered the "sale of human tissue", instead of "cost reimbursement" for preparation.…”
Section: Personal Experiencementioning
confidence: 99%